PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA MIKRO TERKAIT KEBIJAKAN PPKM - Putro, Isyak Pancoro; Purnomo, Sugeng Hadi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This emergency situations cause of covid 19 spreading threat makes government close many kinds of work. Those policy affecting labour income decrease. for that, government must take responsibility in order to fulfilling the daily needs of the labour. this article will talk and give advice to government what should they do